The effect of pericapsular nerve group block and lateral femoral cutaneous nerve block on postoperative recovery after hip arthroplasty - Yuan Tian; Qianqian Lu; Yuxin Yuan; Zhouting Hu; Wangyu Li; Kai Li (Scientific Reports)
Abstract Total hip arthroplasty can cause moderate and severe pain that can have a profound impact during postoperative rehabilitation. Regional nerve block is recommended for anesthesia and analgesia during hip surgery. In particular, the iliac fascia space block of the inguinal ligament is a widely used technique in clinical practice that can block the femoral nerve trunk, obturator nerve trunk, and lateral femoral cutaneous nerve simultaneously. This study aimed to compare the effect of supra-inguinal fascia iliaca compartment block (S-FICB) to a combination of pericapsular nerve group block (PNGB) and lateral femoral cutaneous nerve block (LFCNB) on block range and analgesia as well as motor function of patients with total hip arthroplasty. Sixty patients undergoing total hip arthroplasty through posterolateral approach were randomly divided into two groups with 30 patients each. After complete awakening from general anesthesia, patients received ultrasound-guided S-FICB with 40 mL 0.4% ropivacaine (group S) or 20 mL 0.4% ropivacaine PNGB combined with 3 mL 0.4% ropivacaine LFCNB (PH group). We used the Numerical Rating Scale and cumulative dosage of sufentanil to grade pain during the first 48 h. Quadriceps femoris muscle and adductor muscle strength, range of sensory block, length of stay, and complications were also recorded. No significant differences were found in analgesic indicators of both groups (P>0.05). The Numerical Rating Scale scores of resting pain at each time point after the blockage were significantly lower than those before the blockage (P<0.05). However, the PH group had significantly less incidence of analgesia sensation in the anterior and medial side of the thigh (P < 0.05), and less incidence of quadriceps and adductor weakness (P<0.05) at 1 h and 6 h after the blockage compared to that in group S. Compared to S-FICB, the combination of PNGB and LFCNB provided equivalent analgesic effect and significantly lowered the risk of numbness and muscle weakness of the thigh, which is more conducive to early postoperative exercise and rehabilitation .This combination can be used as a new option in multimodal analgesia after total hip arthroplasty. Trial registration: Chinese Clinical Trial Registry (no. ChiCTR2200055963, date of registration 29/01/2022).